FORMATION OF A RISK MONITORING ALGORITHM AS A TOOL FOR ENSURING THE INCREASING LEVEL OF ECONOMIC SECURITY OF CONSTRUCTION COMPANIES - Fisunenko, Pavlo; Chernysh, Maxim (Current Problems of Sustainable Development, 2025)
Increasing uncertainty in the economic environment and aggravation of geopolitical risks require construction companies to implement progressive methods of risk assessment and management in order to minimize potential losses and ensure business continuity. According to research by the National Institute for Strategic Studies, an effective economic security system involves the integrated application of strategic planning, operational response and control over critical business processes. An effective system of economic security of construction companies should be based on the principles of continuous improvement, responsibility and transparency. Regular monitoring and analysis of risks, as well as the implementation of modern management technologies, allow construction companies to adapt to changes in the external environment and ensure stable development in the long term. An important aspect is the development of methodological support for assessing the economic security of construction companies, taking into account military risks. This involves the development of a system of indicators that allow quantitatively assessing the level of economic security, as well as determining threshold values, when reached which there is a threat to the stable functioning of the enterprise. The results of the study can be used to develop practical recommendations for increasing the economic security of construction companies in martial law, which will contribute to their stability and ability to recover after the end of hostilities.